(untitled) (Advances in Applied Biological Research, 2024)
Bacillus spp. is a rich source of various Secondary Metabolites (SMs) that are used for diverse purposes. These include lipopeptides, non-ribosomal peptides, polyketides and many more which possess strong antimicrobial, antifungal and insecticidal properties thereby making them useful ingredients for biotechnology, agriculture, cosmetics, healthcare and food preservation. This review provides an overview on the current understanding of Bacillus SM’s diversity that has been overlooked to some extent as well as their mode-of-action and application prospects. Recent technological advancements—such as metagenomics, synthetic biology, CRISPR-Cas9, machine learning, microfluidics, and high-throughput screening—have accelerated discoveries and optimized SM production. The use of SMs as plant growth promoting compound in agriculture controlling pathogens while may also have pharmaceutical, nutraceutical and cosmetic applications. Furthermore, they possess a broad range of industrial applications, including use in detergents and food preservatives, offering more versatility and environmental friendliness compared to chemical alternatives. Though there has been significant progress there still exist major knowledge gaps in regulation and ecological roles played by SMs that need to be addressed through research. As we uncover the secrets behind the production and various application of SMs, microorganisms can become effective allies in addressing global challenges for a healthier, more sustainable planet.